La formación para la investigación musical formativa: diversos casos (2015)
This article aims to present an approach to training for formative research in the field of higher education music. The theoretical reference references, mostly derived from the Education Sciences, such as those of Bernardo Restrepo, Ciro Parra and the group of founders of the Colombian Network of Research Seedbeds (Red ColSI), some compilations of Colombian music educators , like Ligia Ivette Asprilla and María Victoria Casas, in addition to the national regulation on the subject, offer a way to go in the teaching dedication in Colombia. It should be noted that currently the academic discussions on musical and artistic research are focused on the research-creation relationship with Colciencias and little is disclosed about formative research or research training, that is, the formation of the research generational relay in music.